A rare pediatric variant of organized hematoma in the maxillary sinus. Issue 4 (July 2015) - Cho, Young Ah; Kwon, Ik Jae; Kim, Soung Min; Myoung, Hoon; Lee, Jong Ho; Lee, Suk Keun
Abstract Organized hematoma of the maxillary sinus is an uncommon, benign, heterogeneous, non-neoplastic, and hemorrhagic lesion characterized by mucosal swelling and bone destruction that can be locally aggressive in the unilateral maxillary sinus. The clinical, radiographical, and pathological characteristics of a 2-year-old patient with an organized hematoma in the maxillary sinus were studied with preoperative computed tomography (CT) and magnetic resonance imaging (MRI) scans and histopathological examination with hematoxylin and eosin (H&E), masson trichrome (MT), and immunohistochemical stainings of vascular markers, such as CD31, factor VIII, and smooth muscle actin (SMA); and lymphatic factors, such as D2-40; and proliferation factors, such as Ki-67 and bcl-2. A total of 17 articles of similar pathology have been reported in the English-language literature under the name of an organized hematoma in the maxillary sinus. We reviewed these retrospective studies of 60 patients who were treated surgically within the past 17 years and found no consensus on the diagnostic criteria of this disease or surgical approaches. Patient age ranged from 11 to 78 years, and the average age was 42.8 years. The ratio of male to female was approximately 2:1, no cases in pediatric patients were found. We report the first case of organized hematoma in the pediatric maxillary sinus with its clinico-radio-pathologic characteristics. Preoperative imaging was essential for the accurate diagnosis of this disease, and sublabial approach combined with endonasal endoscopic confirmation can be also recommended in the pediatric patient.